DNAJB2‐related Charcot‐Marie‐Tooth disease type 2: Pathomechanism insights and phenotypic spectrum widening. (23rd March 2022) - Saveri, Paola; Magri, Stefania; Maderna, Emanuela; Balistreri, Francesca; Lombardi, Raffaella; Ciano, Claudia; Moda, Fabio; Garavaglia, Barbara; Reale, Chiara; Lauria Pinter, Giuseppe; Taroni, Franco; Pareyson, Davide; et al.
Abstract: Background and purpose: Mutations in DNAJB2 are associated with autosomal recessive hereditary motor neuropathies/ Charcot‐Marie‐Tooth disease type 2 (CMT2). We describe an Italian family with CMT2 due to a homozygous DNAJB2 mutation and provide insight into the pathomechanisms. Methods: Patients with DNAJB2 mutations were characterized clinically, electrophysiologically and by means of skin biopsy. mRNA and protein levels were studied in lymphoblastoid cells (LCLs) from patients and controls. Results: Three affected siblings were found to carry a homozygous DNAJB2 null mutation segregating with the disease. The disease manifested in the second to third decade of life. Clinical examination showed severe weakness of the thigh muscles and complete loss of movement in the foot and leg muscles. Sensation was reduced in the lower limbs. All patients had severe hearing loss and the proband also had Parkinson's disease (PD). Nerve conduction studies showed an axonal motor and sensory length‐dependent polyneuropathy. DNAJB2 expression studies revealed reduced mRNA levels and the absence of the protein in the homozygous subject in both LCLs and skin biopsy. Interestingly, we detected phospho‐alpha‐synuclein deposits in the proband, as already seen in PD patients, and demonstrated TDP‐43 accumulation in patients' skin. Conclusions: Our results broaden the clinical spectrum of DNAJB2 ‐related neuropathies and provide evidence that DNAJB2 mutations should be taken into account as another causative gene of CMT2 with hearing loss and parkinsonism. The mutation likely acts through a loss‐of‐function mechanism, leading to toxic protein aggregation such as TDP‐43. The associated parkinsonism resembles the classic PD form with the addition of abnormal accumulation of phospho‐alpha‐synuclein. Abstract : We report a family with Charcot‐Marie‐Tooth disease type 2 (CMT2), with hearing loss and parkinsonism, who harbor a novel homozygous DNAJB2 mutation, expanding the phenotype associated with the disease and providing new insights into its pathomechanism.